1982
DOI: 10.1029/wr018i004p01143
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐ and atmosphere‐induced plant water stress in cotton as inferred from foliage temperatures

Abstract: Foliage temperatures of cotton obtained by means of infrared thermometry, along with air wet and dry bulb temperature measurements, were used to investigate certain relationships existing between the water contents of soil and air and the ability of the crop to maintain transpiration at the potential rate. It was found that as soil water content is progressively depleted fo!lowing an irrigation, departure from potential transpiration begins to occur at smaller and smaller values of air vapor pressure deficit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 13 publications
1
36
0
1
Order By: Relevance
“…While this value of the upper limit was obtained from a small number of measurements, it was obtained on a canopy of similar architecture adjacent to the experimental plots. The value so obtained is similar to values for other crops (Jackson et al, 1981;Idso et al, 1982a;Jackson, 1982) and is reasonably close to that found for cotton by Idso et al (1982b).…”
Section: Theorysupporting
confidence: 74%
See 2 more Smart Citations
“…While this value of the upper limit was obtained from a small number of measurements, it was obtained on a canopy of similar architecture adjacent to the experimental plots. The value so obtained is similar to values for other crops (Jackson et al, 1981;Idso et al, 1982a;Jackson, 1982) and is reasonably close to that found for cotton by Idso et al (1982b).…”
Section: Theorysupporting
confidence: 74%
“…To interpret the effect of the flooding on the canopy temperature, we followed the method of Jackson et al (1983), Jackson (1982) and Idso et al (1982a) in developing a stress index. In order to avoid confusion with the Crop Water Stress Index (CWSI) defined by them for studying crop response to soil water deficits, we define a more general Crop Stress Index (CSI) that encompasses plant stress as a result of short-term flooding.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the diurnal change in this error has been shown for a number of species (Turner and Long, 1980) the relationship to atmospheric evaporative demand, as measured by the air vapor pressure deficit (AVPD), has not been shown. This note examines this relationship for cotton and the effect that the error has on the sensitivity of the relationship between the plant water stress index derived from canopy temperature measurements and the soil-induced plant water potential as shown by Idso et al (1982).…”
Section: Introductionmentioning
confidence: 99%
“…The soil-induced component of the leaf pressure potential of cotton (Gossypium hirsutum L.) can be underestimated in absolute magnitude by up to 44% if ~x exp values are used in the calculation. Removing this error by using ~x enc values subsequently improves both the discriminating ability of the plant water stress index proposed by Idso et al (1982) and the accuracy of the estimate of the soil-induced component of leaf xylem pressure potential. …”
mentioning
confidence: 99%